PERAN KEPEMIMPINAN ADAT DALAM PENYELESAIAN PIUTANG BUWUH DI DUSUN GUNUNG MALANG KABUPATEN PASURUAN - Reviandy Azhar Ramdhani; Muhammad Nafis Rojabi; Moch. Chusni Mubarok; Nur Kholis; Firza Agung Prakoso; Tristan Rokhmawan (Realism: Law Review, 2024)
Abstract This article discusses the important role of Indigenous leadership in debt settlement in Gunung Malang Hamlet, Pasuruan Regency. Buwuhan debt, which is based on local indigenous traditions, has become a serious problem in the region, creating significant economic and social pressure. This study uses a qualitative approach with a case study method to identify the role of Indigenous leadership, strategies used, and community responses to debt settlement efforts. The results showed that adat leadership plays an important role as a mediator and facilitator in debt settlement Buhuhan. They use a deliberative and mutual aid approach to find a fair solution for all parties involved. Although faced with obstacles and challenges, Buwuhan debt settlement efforts led by Indigenous leadership are considered effective by the community in general. The community's positive response to the role of Indigenous leadership reflects recognition of the moral authority and influence that Indigenous leadership has in mediating and resolving conflicts related to the Buhuhan debt. This research has important implications both academically and practically. Theoretically, this study enriches the understanding of the role of Indigenous leadership in debt settlement Buwuhan, while in practical terms, the implications can help in the development of debt settlement strategies Buwuhan more effective in Pasuruan and other regions facing similar problems. Keywords: Indigenous leadership, debt settlement Buwuhan, Mount Malang Hamlet, Pasuruan, deliberation